LITERASI KEUANGAN, SIKAP KEUANGAN, TEKNOLOGI KEUANGAN DAN GAYA HIDUP TERHADAP PERILAKU KEUANGAN MAHASISWA - Mohtar Khudori; Endarwati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Financial literacy is information about financial institutions, confidence in pledging funds to financial institutions, and the ability to utilize financial services to achieve good financial management. Financial attitude is the way an individual or organization treats and manages finances. Financial technology is a combination of financial industry systems and technologies that enable the buying or selling of products or services at different times and in different market spaces. Lifestyle is a person's lifestyle expressed through their activities, interests and views on spending money and how they allocate their time. Financial behavior is an individual's ability to manage their daily finances. The aim of this research is to determine the influence of financial literacy, financial attitudes, financial technology and lifestyle on financial behavior. Sampling in this study used a questionnaire method with a total of 110 respondents. Data were analyzed using a quantitative approach using the SAMPLS application. The results of this research show that financial technology, financial attitudes, financial technology do not have a significant effect on financial behavior, while lifestyle has a significant effect on financial behavior. For future researchers who will later conduct research by developing the Technolgy Acceptance Model (TAM), it is hoped that they will be able to add other factors, so that they can find out other factors that influence society in the process of adopting a technological system.